TES MINAT DAN BAKAT: PERAN DALAM BIMBINGAN DAN KONSELING KARIER - Aulia, Ananda eka; Sani Sevy Febriana; Shafika Ayudyah Lestari (MERDEKA : Jurnal Ilmiah Multidisiplin, 2025)
Guidance and counseling teachers play a very important role in providing support to students at school. One effective tool to help students determine their career path is the use of interest and aptitude tests. Interest tests are designed to recognize fields or activities that an individual is passionate about, while aptitude tests are used to evaluate a person's natural potential or abilities. This research aims to improve the quality of students' decisions regarding major selection and direct them to areas of work that match their abilities, which in turn can increase the chances of future success. The method used in this study is a literature study, which aims to collect and analyze information from various relevant written sources. Literature study is the process of searching, reading, and analyzing books, articles, journals, and other scientific documents related to research topics to gain a deeper understanding. The results of this study include: (1) Definition of Interest and Aptitude Tests, (2) Types of Interest and Aptitude Tests, (3) Factors Influencing Interest and Aptitude Tests, (4) Objectives of Career Guidance and Counseling, (5) The Role of Interest and Aptitude Tests in Career Guidance, (6) Practical Approaches in the Implementation of Tests, (7) Challenges in the Implementation of Interest and Aptitude Tests, (8) Benefits of Using Interest and Aptitude Tests in Career Guidance.